Effects of Alarm System Error Bias and Reliability on Performance Measures in a Multitasking Environment: Are False Alarms Really Worse than Misses?. (September 2017) - Chancey, Eric T.; Yamani, Yusuke; Brill, J. Christopher; Bliss, James P.
Researchers suggest signaling system false alarms damage human performance more than misses, yet the evidence is inconsistent. Therefore, we examined the effects of false alarm and miss rates on concurrent task and detection task performance. Method : Eighty-eight participants interacted with two primary flight simulation tasks and a secondary detection task, with the help of a signaling system that varied by error bias (false alarm-prone, miss-prone) and reliability (90%, 60%). Results : Higher reliability led to better detection task performance and the miss-prone group had higher dependence rates. Misses, however, negatively affected detection task performance more than false alarms and Bayes analyses indicated no differential effect of error type on primary task performance. Conclusion : The frequent alarms in the false alarm-prone group appeared to aid participants in switching from the primary to secondary detection task. Participants may have used the information acquisition function of the aid, but not the information analysis function.